2017
DOI: 10.1088/1741-4326/aa687e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of protruding surfaces in the JET divertor

Abstract: Abstract. Tungsten (W) melting is a major concern for next step fusion devices. Two ELM induced tungsten melting experiments have been performed in JET by introducing two special target plate lamellae designed to receive excessively high ELM transient power loads. The first experiment was performed in JET in 2013 using a special lamella with a sharp leading edge gradually varying from h = 0.25 mm to 2.5 mm in order to maximise the temperature rise by exposure to the full parallel heat flux. ELM-induced transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Leading edge melting experiments conducting on JET in 2013 challenged the validity of this approximation by finding initially that the experimentally derived Q s on the side of a protruding W lamella in the bulk W outer divertor needed to be reduced by a factor ~5 under L-mode conditions to be consistent with 3D thermal modelling of the observed top surface temperature of the lamella performed with the MEMOS-3D code [5]. Although these discrepancies have recently been resolved through much more detailed thermal analysis using improved techniques [6,7], the initial discrepancy stimulated a great of additional effort on other devices, within the ITPA coordinated activity to investigate the validity of the OA. As part of this effort, dedicated experiments have been performed on the COMPASS tokamak (R = 0.56 m, a = 0.2 m) to thoroughly study the heating of misaligned poloidal gap (PG) edges.…”
Section: Heat Loads On Poloidal and Toroidal Edges Of Castellated Pla...mentioning
confidence: 99%
“…Leading edge melting experiments conducting on JET in 2013 challenged the validity of this approximation by finding initially that the experimentally derived Q s on the side of a protruding W lamella in the bulk W outer divertor needed to be reduced by a factor ~5 under L-mode conditions to be consistent with 3D thermal modelling of the observed top surface temperature of the lamella performed with the MEMOS-3D code [5]. Although these discrepancies have recently been resolved through much more detailed thermal analysis using improved techniques [6,7], the initial discrepancy stimulated a great of additional effort on other devices, within the ITPA coordinated activity to investigate the validity of the OA. As part of this effort, dedicated experiments have been performed on the COMPASS tokamak (R = 0.56 m, a = 0.2 m) to thoroughly study the heating of misaligned poloidal gap (PG) edges.…”
Section: Heat Loads On Poloidal and Toroidal Edges Of Castellated Pla...mentioning
confidence: 99%
“…Using this heat-flux one should then be able to calculate the temperature evolution using forward analysis based on finite element methods. A very detailed analysis of geometrical factors was undertaken [38] and also detailed forward modelling was performed [38,39]. It was shown that, at least in L-mode, the assumption of optical heat flux projection is justified and for H-Mode the measured heat-flux can be reasonably well matched to allow forward modelling of the melt geometry.…”
Section: Ilw-3 Experimentsmentioning
confidence: 99%
“…Further work is ongoing, however it is clear that for both L-Mode and H-Mode accurate determination of geometries and incorporation of them into the models allows to explain the mitigation factors within the uncertainties. More details are given in [38,39]…”
Section: Ilw-3 Experimentsmentioning
confidence: 99%
“…A series of experiments [6] was conducted in the COMPASS tokamak with a specially designed graphite inner wall limiter (IWL). In JET, running with an ITER-like wall, a sharp edge [7] and a protruding [8] W lamella (15° slope), were exposed to L-mode [9] and H-mode [10] plasmas. On ASDEX-Upgrade, an extensive series of experiments in H-mode were performed on misaligned and 15° sloped tiles using its Divertor Manipulator II system (DIM-II) up to 1.1 mm to observe tungsten melt motion [11].…”
Section: Withmentioning
confidence: 99%